Agricultural technology, risk, and gender: a CGE analysis of Mozambique - Arndt, Channing; Tarp, Finn (Elsevier, 2000)
Interactions between agricultural technology improvements, risk-reducing behavior, and gender roles in agricultural production in Mozambique are examined. The analysis employs a computable general equilibrium (CGE) model that explicitly incorporates key features of the economy. These include: detailed accounting of marketing margins, home consumption, risk, and gender roles in agricultural production. Our results show that agricultural technology improvements benefit both male and female occupants of rural households. Due to economic interactions, agricultural technology improvements are particularly compelling when combined with marketing system improvements. Moreover, technological change in cassava appears to be a particularly strong lever for increasing female and overall household welfare, especially when risk is considered.--from Abstract.